Design-of-Experiment Based Systematic Tuning of Square Open Loop Resonator - Teguh Prakoso; Imam Santoso; Munawar Riyadi (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Stub-loaded, square open loop resonator (SOLR) is a type of bandpass filter with dual-band response. It is believed that its center frequency values are determined by entire length of open loop resonator’s and open stub's lengths, the bandwidth values are determined by coupling between two resonators. However, design of experiments (DOE) method applied in this paper shows that the center frequency values are also affected by interaction between resonator length, stub length, and distance between the two resonators in pair. The DOE also shows that bandwidth values, both upper and lower bands, are not only affected by the distance between resonators but also by the resonator’s and stub’s lengths. Utilizing slope values of the significant factors, systematic tuning to SOLR can be done. With few steps, small error on frequency responses can be obtained.